Innate immune complexity in the purple sea urchin: diversity of the Sp185/333 system - Smith, L. C. (Frontiers in Immunology, 2012)
The California purple sea urchin, Strongylocentrotus purpuratus, is a long-lived echinoderm with a complex and sophisticated innate immune system. There are several large gene families that function in immunity in this species including the Sp185/333 gene family that has ∼50 (±10) members. The family shows intriguing sequence diversity and encodes a broad array of diverse yet similar proteins. The genes have two exons of which the second encodes the mature protein and has repeats and blocks of sequence called elements. Mosaics of element patterns plus single nucleotide polymorphisms-based variants of the elements result in significant sequence diversity among the genes yet maintains similar structure among the members of the family. Sequence of a bacterial artificial chromosome insert shows a cluster of six, tightly linked Sp185/333 genes that are flanked by GA microsatellites. The sequences between the GA microsatellites in which the Sp185/333 genes and flanking regions are located, are much more similar to each other than are the sequences outside the microsatellites suggesting processes such as gene conversion, recombination, or duplication. However, close linkage does not correspond with greater sequence similarity compared to randomly cloned and sequenced genes that are unlikely to be linked. There are three segmental duplications that are bounded by GAT microsatellites and include three almost identical genes plus flanking regions. RNA editing is detectible throughout the mRNAs based on comparisons to the genes, which, in combination with putative post-translational modifications to the proteins, results in broad arrays of Sp185/333 proteins that differ among individuals. The mature proteins have an N-terminal glycine-rich region, a central RGD motif, and a C-terminal histidine-rich region. The Sp185/333 proteins are localized to the cell surface and are found within vesicles in subsets of polygonal and small phagocytes. The coelomocyte proteome shows full-length and truncated proteins, including some with missense sequence. Current results suggest that both native Sp185/333 proteins and a recombinant protein bind bacteria and are likely important in sea urchin innate immunity.